2014
DOI: 10.14419/ijans.v3i2.2412
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Preterm Infants’ Night Sleep: and Online Community-Based Survey of Maternal Factors and Perceptions of Infants’ Nighttime Awakenings and Sleep Problems

Abstract: Background: Between one-quarter and one-third of infants aged six months to five years have sleeping problems.  Infants' night sleep patterns, in particular problematic night waking with crying, are a common concern for parents.  Many factors can influence the development of infants’ night sleep patterns and sleep problems, including parental interaction. Objectives: To examine the associations between premature infants’ nighttime awakening, mothers’ reports of sleep problem severity, and maternal factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Infants' sleep patterns are problematic and include night waking with crying, a common concern for parents of infants. In previous studies, the mean frequency of nocturnal waking of full-term infants was 0.8/night (range, 0-2.9/night); just over half (55%) of the participating mothers reported that their premature infants woke 2.1 times per night for a mean 45.7 minutes per night, which is similar to our findings [29,30]. We found that the frequency and duration of night wakings of premature infants affected the quality of the maternal sleep.…”
Section: Discussionsupporting
confidence: 91%
“…Infants' sleep patterns are problematic and include night waking with crying, a common concern for parents of infants. In previous studies, the mean frequency of nocturnal waking of full-term infants was 0.8/night (range, 0-2.9/night); just over half (55%) of the participating mothers reported that their premature infants woke 2.1 times per night for a mean 45.7 minutes per night, which is similar to our findings [29,30]. We found that the frequency and duration of night wakings of premature infants affected the quality of the maternal sleep.…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, training regarding safety measures may be particularly useful in this situation because of the risk of rocking the baby too fast on the mother's legs or causing the baby to fall when the mother is rocking him/her. The children in this study has frequent awakinings as expected (15,26). According to this study 40.5% of children 1-2 times, and 34.0 of children 3-4 times wake up overnight.…”
Section: Child's Sleep Patternssupporting
confidence: 62%
“…A study with 0-3 years old children, conducted in our country, reported sleep problems at 18.8% (14). The majority of the mothers who participated in another study reported that they considered their babies to have sleep problems and that the problem was serious (15). In another study, 17.33% of mothers from predominantly Asian countries reported severe sleep problems, and 34.57% reported minor sleep problems.…”
Section: Parental Perception Of the Child's Sleepmentioning
confidence: 95%
See 1 more Smart Citation
“…An infant’s individual needs relating to sleep may be influenced by his or her genetics (Fisher, van Jaarsveld, Llewellyn, & Wardle, 2012), birth weight, preterm birth (Asaka & Takada, 2010), and chronological age (Galland et al, 2012). Over half of mothers of preterm infants consider their infant’s sleep to be problematic at 5 to 6 months of age (Ali, Hall, Warnock, Wong, & Ratner, 2014). Meanwhile, a caregiver’s interactions with the infant and ability to optimally meet the child’s unique needs may be influenced by separation anxiety (Scher, 2008) and the parent’s own attachment status (Benoit, Zeanah, Boucher, & Minde, 1992), as well as parental age and education level (Oxford & Findlay, 2013).…”
Section: Proposed Theorymentioning
confidence: 99%